2013
DOI: 10.1073/pnas.1303312110
|View full text |Cite
|
Sign up to set email alerts
|

Language can boost otherwise unseen objects into visual awareness

Abstract: Linguistic labels (e.g., "chair") seem to activate visual properties of the objects to which they refer. Here we investigated whether language-based activation of visual representations can affect the ability to simply detect the presence of an object. We used continuous flash suppression to suppress visual awareness of familiar objects while they were continuously presented to one eye. Participants made simple detection decisions, indicating whether they saw any image. Hearing a verbal label before the simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
248
4
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 248 publications
(302 citation statements)
references
References 73 publications
27
248
4
2
Order By: Relevance
“…In this paradigm, one eye views constantly changing Mondrian-style images (which initially dominate conscious perception), while the other eye views an image of an object. Pinto and colleagues (2015) found that expected objects broke through the continuous flash suppression faster than unexpected, or neutral objects (see also Chang, Kanai, & Seth, 2015;Lupyan & Ward, 2013). Together, findings from these studies suggest that participants were not just biased towards reporting the preferred stimuli, but actually were more likely to perceive the stimuli that they wanted or expected to see.…”
mentioning
confidence: 59%
“…In this paradigm, one eye views constantly changing Mondrian-style images (which initially dominate conscious perception), while the other eye views an image of an object. Pinto and colleagues (2015) found that expected objects broke through the continuous flash suppression faster than unexpected, or neutral objects (see also Chang, Kanai, & Seth, 2015;Lupyan & Ward, 2013). Together, findings from these studies suggest that participants were not just biased towards reporting the preferred stimuli, but actually were more likely to perceive the stimuli that they wanted or expected to see.…”
mentioning
confidence: 59%
“…16 The uncertainty inherent in language promotes the formation-in both developmental time and in the moment-of representations that represent category diagnostic information and abstract over idiosyncratic information. The consequences of these more categorical representations are substantial, spanning basic perceptual tasks (Lupyan, 2008;Lupyan & Spivey, 2010a, 2010bLupyan & Ward, 2013;Lupyan & Spivey, 2008) and higher level reasoning (Lupyan, 2015).…”
Section: Knowledge Through Language Versus Knowledge Through Perceptimentioning
confidence: 99%
“…We mentally represent things that are present in the environment during online processing of real-world perception and action, and can represent them again in their absence during offline remembering, planning, and daydreaming (Wilson, 2002). As such, it seems reasonable that attaching a linguistic label to a particular aspect of experience could make it easier to perform some conceptual tasks, such as acquiring concepts like object kinds (Xu, 2002) and numbers (Carey, 2004), shaping the boundaries between colour categories (Winawer et al, 2007), or influencing how easily a visual feature or object is detected (Lupyan & Ward, 2013). Attaching a label to a bundle of experience may allow us to attend to it more easily in online processing, re-activate it more easily in offline processing, and hence help it cohere into a concept by assisting with abstraction (i.e., moving from a specific instance of sensorimotor experience to a generalised, aggregate form).…”
Section: What Have Labels Ever Done For Us? the Linguistic Shortcut Imentioning
confidence: 99%